Multistaged In Silico Discovery of the Best SARS-CoV-2 Main Protease Inhibitors amongst 3009 Clinical and FDA-Approved Compounds - Ibrahim H. Eissa; Abdulrahman M. Saleh; Sara T. Al-Rashood; Abdul-Aziz M. M. El-Attar; Ahmed M. Metwaly (Journal of Chemistry)
As a follow-up to our teamwork’s former work against SARS-CoV-2, eight compounds (ramelteon (68), prilocaine (224), nefiracetam (339), cyclandelate (911), mepivacaine (2325), ropivacaine (2351), tasimelteon (2384), and levobupivacaine (2840)) were revealed as the best potentially active SARS-CoV-2 inhibitors targeting the main protease (PDB ID: 5R84), Mpro. The compounds were named in the midst of 3009 FDA and clinically approved compounds employing a multistaged in silico method. A molecular fingerprints study with GWS, the cocrystallized ligand of the Mpro, indicated the resemblance of 150 candidates. Consequently, a structure similarity experiment disclosed the best twenty-nine analogous. Then, molecular docking studies were done against the Mpro active site and showed the binding of the best compounds. Next, a 3D-pharmacophore study confirmed the obtained results for the eight compounds by exhibiting relative fit values of more than 90% (except for 68, 74%, and 2384, 83%). Levobupivacaine (2840) showed the most accurate docking and pharmacophore scores and was picked for further MD simulations experiments (RMSD, RMSF, Rg, SASA, and H-H bonding) over 100 ns. The MD simulations results revealed the accurate binding as well as the optimum dynamics of the Mpro-levobupivacaine complex. Finally, MM-PBSA studies were conducted and indicated the favorable bonding of the Mpro-levobupivacaine complex with a free energy value of −235 kJ/mol. The fulfilled outcomes hold out hope of beating COVID-19 through more in vitro and in vivo research for the named compounds.